Impact of a history of maternal depression and anxiety on asthma control during pregnancy. (9th August 2017) - Grzeskowiak, Luke E.; Smith, Brian; Roy, Anil; Schubert, K. Oliver; Baune, Bernhard T.; Dekker, Gustaaf A.; Clifton, Vicki L.
ABSTRACT: Objective : To determine the impact of self-reported maternal depression/anxiety on asthma control during pregnancy. Method : Pregnant women with a doctor diagnosis of asthma (n = 189) were prospectively recruited at their antenatal booking visit, and the presence of maternal depression and anxiety was identified using self-report and routine questionnaire assessments. Data on exacerbations and asthma control were collected during gestation. Asthma control was assessed using the Juniper Asthma Control Questionnaire (ACQ) and women were classified as having recurrent uncontrolled asthma if their ACQ score was >1.5 during two or more consecutive study visits. Exacerbations were defined as events that led to increased treatment requirements, and doctor or hospital visits. Results : There were 85 women with self-reported depression/anxiety and 104 women without self-reported depression/anxiety. The presence of depression/anxiety was associated with an increased likelihood (adjusted hazard ratio (HR) 1.67: 95% confidence interval (CI) 1.03–2.72) and incidence (adjusted incidence rate ratio (IRR) 1.71: 95% CI 1.13–2.58) of uncontrolled asthma during pregnancy, as well as an increased risk of recurrent uncontrolled asthma during 2 or more study visits (adjusted relative risk (RR) 1.98: 95% CI 1.00–3.91). No impact of depression/anxiety was observed with respect to the likelihood (adjusted HR 0.70: 95% CI 0.35–1.41) or incidence of exacerbations during pregnancy (adjusted IRR 0.66: 95% CI 0.35–1.26). Conclusions : This study provides evidence that the presence of maternal depression/anxiety is associated with an increased likelihood and incidence of uncontrolled asthma during pregnancy. Given the high prevalence of co-morbid depression/anxiety among asthmatics, further research investigating such associations is urgently required.